(untitled) (Homoeopathy for All, 2021)
Urinary tract infection (UTI) is the third most common bacterial infection in India.1Women are more prone to get UTI. Most of the women experienced at least one episode of UTI in their lifetime.2It is one of the common reasons for adults to seek medical help and is one of the most frequently occurring nosocomial infections.3150 million people are diagnosed worldwide with UTI every year, which is costing 6 billion US dollars on the global economy.4Escherichia coli (E.coli) is the most common bacteria responsible for the both the community acquired and the hospitalized UTI patients.5 In the recent years, it has been noticed that bacterial resistance to a large number of antibiotics is causing major health concerns.6The Extended Spectrum Beta Lactamases, shortly called as ESBLs,which hydrolyse the oxyimino beta lactams like cefotaxime, ceftazidime, monobactum and ceftriaxone without any effect on the cephamycins, carbapenem and related compounds, have emerged as an important mechanism of resistance amongst these uropathogens.7 On the other hand, homoeopathic does not have the issue of microbial resistance. Its treatment modality with holistic approach not only found effective to manage such cases but also to prevent from the occurrence. In this article, we have discussed about the role of homoeopathy in antibiotic resistant UTIs.